Teaching the indigenous students with courseware based on theory of multiple intelligences - Mokhsin Misron, Mudiana; Shaffiei, Zatul Amilah; Suhadak, Saiful Adli; Abdul Mutalib, Ariffin (Science Publications, 2011)
Problem statement: This study reports result of a research carried out to determine the possibility of computer technology use among the indigenous children in teaching and learning.Approach: In this study, courseware was used in a classroom of a school for the indigenous children, in which their motivation was extremely low.Comparison between normal class and courseware-assisted class was carried out and reports in the methodology.The courseware was tested to meet the requirements of Multiple Intelligences (MI) Theory.Results: The findings reveal that the indigenous children were able to accept the newly-introduced courseware-assisted teaching and learning which includes the eight types of intelligences.This could be seen in their attendance record and achievement improvement. Conclusion/Recommendation: This study concludes that the courseware could be a usable tool to support the indigenous learning motivation.